Analysis of Cardiovascular Endurance of Futsal Athletes for Youth Development in Bengkulu City - Afif Hofizar Sahrun; Andika Prabowo; Bogy Restu Ilahi (SPORT GYMNASTICS : Jurnal Ilmiah Pendidikan Jasmani, 2022)
This study aims to determine the level of cardiovascular endurance of young futsal athletes in the city of Bengkulu. This type of research is descriptive research. The research sample amounted to 30 people. The instrument used in this study was to use the Bleep Test/Multi-Stage which was carried out in the field with a length of 20 meters. The VO2 Max test was carried out by 30 Futsal Players for Youth Development in Bengkulu City. Based on the above results it can be concluded that the VO2 Max ability of the overall Youth Development Futsal Players in Bengkulu City carried out by 30 players in the Medium category as many as 16 players or with a percentage of 53%. With these results, it can be said that the cardiovascular results of Youth Development Futsal Players in Bengkulu City are in the medium category.Keywords: : Futsal Athletes, Cardiovascular Endurance